Being, time, bios : capitalism and ontology - Kordela, Aglaia Kiarina, 1963- (SUNY series, insinuations., 2013)
"Although both share a focus on human life as it is inscribed by power, Foucauldian biopolitics and Lacanian psychoanalysis have remained isolated from and even opposed to one another. In Being, Time, Bios, A. Kiarina Kordelaaims to overcome this divide, formulating a historical ontology that draws from Spinoza, Marx, Heidegger, and Sartre to theorize the changed character of "being" and "time" under secular capitalism. With insights from film theory, postcolonial studies, and race theory, Kordela's wide-ranging analysis suggests a radically new understanding of contemporary capitalism--one in which uncertainty, sacrifice, immortality, and the gaze are central."--Publisher's website.